Implementation Strategy of Indonesia Sustainable Palm Oil (ISPO) Certification: A'WOT Analysis Approach - Ahmad Zainuddin; Fuad Muchlis; Resti Prestika Destiarni; Ahmad Syariful Jamil; Araz Meilin; Dwi Nurul Amalia; Muhammad Abdul Aziz (Jurnal Ilmu Pertanian Indonesia, 2025)
The Indonesian Sustainable Palm Oil (ISPO) program was established in 2011 in response to the adverse environmental impacts caused by the expansion of palm oil production in Indonesia. To date, the ISPO implementation in Jambi Province is still relatively low. This is because there are many weaknesses and challenges in implementing the ISPO. This study aimed to identify implementation strategies for sustainable palm oil certification in Jambi Province. This analysis uses the A'WOT approach, which integrates the Analytical Hierarchy Process (AHP) and SWOT analysis. Based on the A'WOT analysis, 23 external and internal factors were obtained, which are strengths, weaknesses, opportunities, and threats. In addition, the A’WOT analysis results show that the priority strategy that can be implemented is to involve MBKM (Merdeka Belajar-Kampus Merdeka, Freedom of Learning-Independent Campus) students in helping farmers. This strategy is because independent smallholders' understanding of ISPO is low and the number of ISPO extension workers or assistants is also limited. Therefore, the choice of strategy that can improve understanding of ISPO implementation is to involve MBKM students to help provide counseling and understanding related to ISPO. Keywords: AHP, independent smallholders, ISPO, oil palm, SWOT